Laparoscopic-assisted resection of jejunal GIST with Acute Gastrointestinal Bleed - Khan, Imran Abdullah; Ganapathi, Senthil Kumar; Rajapandian, Subbiah; Palanivelu, Chinnusamy (Indian Journal of Case Reports, 2020)
Small intestinal bleeding accounts for about 5-10% of gastrointestinal bleed. Jejunal GIST’s though can be a cause but rarely present with acute bleed. The diagnosis of such cases can be quite challenging and requires a multidisciplinary approach. We present a case of acute bleed from jejunal GIST that was managed by laparoscopic-assisted resection. The postoperative period was uneventful and the patient was discharged on day four. Histopathological examination of the specimen was suggestive of GIST that was confirmed further with immunohistochemical staining.